2018
DOI: 10.1089/thy.2017.0685
|View full text |Cite
|
Sign up to set email alerts
|

The Bethesda System for Reporting Thyroid Cytopathology Explained for Practitioners: Frequently Asked Questions

Abstract: For each frequently asked question, an answer is provided based on the literature, the authors' experience, the new version of TBSRTC, and the new World Health Organization classification of tumors of endocrine organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…Our laboratory reported an AUS:malignancy ratio of 2.94, suggesting the appropriate use of the AUS category. In comparison, our literature review of AUS/FLUS use rates demonstrated rates of use of 2.1% to 26%, with a respective ROM of 13% to 43% (Table ) when not considering NIFTP in the ROM, which the findings of the current study are consistent with. The reason for this increased rate can be due to the heterogeneity of the AUS/FLUS category, selection bias for surgery, and known general overuse of this category .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our laboratory reported an AUS:malignancy ratio of 2.94, suggesting the appropriate use of the AUS category. In comparison, our literature review of AUS/FLUS use rates demonstrated rates of use of 2.1% to 26%, with a respective ROM of 13% to 43% (Table ) when not considering NIFTP in the ROM, which the findings of the current study are consistent with. The reason for this increased rate can be due to the heterogeneity of the AUS/FLUS category, selection bias for surgery, and known general overuse of this category .…”
Section: Discussionsupporting
confidence: 86%
“…NIFTP previously was known as noninvasive encapsulated follicular variant of PTC, and has been recognized by the World Health Organization as a tumor with a low potential for malignancy in comparison with conventional PTC . Subsequently, when calculating the ROM, the ranges were found to have a tendency to decrease from a ROM of 10% to 30% to a ROM of 6% to 18% when changes consistent with NIFTP were found on surgical histopathology in TBSRTC II (Table ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that among the false-positive cases, 5 cases were suspicious for PTC, and one case was diagnosed as PTC based on the frozen section analysis. Massimo et al [64] explained that there are two main limitations for frozen section analysis. First, the quality of the specimen obtained for a frozen section is lower than that obtained during routine histopathological examination.…”
Section: Intraoperative Frozen Examination In Misdiagnosed Casesmentioning
confidence: 99%
“…Furthermore, the validation and clinical implementation of these assays require collaborative efforts by the cytopathologist community. Finally, Dr. Massimo Bongiovanni (Vaudois University Medical Center, Lausanne, Switzerland) chaired an interactive “frequently asked questions” session regarding TBSRTC to increase the clinicians’ awareness of the diagnostic criteria behind the categories, ROM, and patient management …”
Section: Introductionmentioning
confidence: 99%